The reorientation of public service motivation: through the lens of SDT - Xu, Chengwei; Haque, Ariful; Chen, Chung-An (2016)
Public service motivation (PSM), or literally “the motivation to serve the public”, is a form of prosocial motivation. It was proposed back in 1990 as a major research theme in public administration within the scope of altruism. It refers to people’s commitment to the public interest, compassion, and interest in policy making.However, this is misleading as prosocial motivation is never purely altruistic in nature. For example, many high-rank public officials make public policies simply due to media pressure or public scrutiny.Therefore, we use the motivational typology in self-determination theory (SDT) to explore the egoistic side of PSM. Our new SDT-based approach shows that there should not be a universal measurement tool for PSM. Scholars need to first identify a given public service behavior, and then develop measures for intrinsic motivation, identified regulation, introjected regulation, and external regulation for this behavior.